Infrastrukturen - Harms, Arne (Dialektik des Globalen. Kernbegriffe, 2019)
Why reflect on infrastructures? Today, we are experiencing a breathtaking expansion and intensification of infrastructural interconnections around the globe. At the same time, infrastructures have also become the explicit subject of research studies in the social sciences and humanities. Accordingly, the thesis of this essay is that infrastructures are the instruments and media of Verräumlichung (spatialization).